Analysis of factors associated with the onset of preeclampsia in pregnant women in Kotabaru District, South Kalimantan Province - Arianti, Dewi; Yuliani, Istri; Risnawati, Risnawati; Maimunah, Siti; Gunarmi, Gunarmi (Science Midwifery, 2025)
Background: South Kalimantan with an MMR of 145 deaths per 100,000 KH. The number of maternal deaths due to preeclampsia is 10 cases. Kotabaru with the second highest number of maternal deaths with a total of 14 cases and there were 6 cases in 2023. Early-onset preeclampsia is preeclampsia that occurs before 34 weeks of gestation and late-onset preeclampsia. The aim of the study was to analyse the correlation of risk factors with the onset of preeclampsia in pregnant women in Kotabaru District. Research Methods: Analytical observational research with cross sectional research design after obtaining approval from the ethics commission of Stikes Guna Bangsa Yogjakarta No. 023/KEPK/IX/2024. All preeclampsia pregnant women in 2023 as many as 148 preeclampsia pregnant women's data were taken and recorded, then chi squared analysis and multiple logistic regression were carried out. Results: The results showed there was an association between parity (p value = 0.001), BMI (p value = 0.017), multiple pregnancy (p value = 0, 025) with the onset of preeclampsia. The results of multiple logistic regression analysis showed the variable parity p value = 0.001 and Exp B (3, 975) and 95% CI 1.811 - 8.401 is the most dominant factor associated with the onset of preeclampsia. Conclusion: There is an association between parity, BMI, and multiple pregnancy with the onset of preeclampsia. The most dominant factor associated is parity. The implications of the research results are that the community is more active in participating in maternal and child health programs, and disseminating information about preeclampsia to other pregnant women, providing iron-enriching and providing calcium tablets to mothers from the first trimester of pregnancy if they are anemic, integrated ANC services.